Simultaneous localization and mapping for mobile robots introduction and methods - d; d; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book investigates the complexities of the theory of probabilistic localization and mapping of mobile robots as well as providing the most current and concrete developments"--Provided by publisher.
Introduction -- Robotic bases -- Probabilistic bases -- Statistical bases -- Robot motion models -- Sensor models -- Mobile robot localization with recursive Bayesian filters -- Maps for mobile robots: types and construction -- The Bayesian approach to SLAM -- Advanced SLAM techniques.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed September 20, 2012).
Keywords: Mobile robots; Geographical positions; Localization theory; Feature sensors; Map sensors; Mobile robot localization; Non-holonomic model; Probabilistics; Robotics; Simultaneous localization and mapping (SLAM); Electronic books